Liberia: Availability of data on nutrition intervention coverage - Transform Nutrition West Africa (International Food Policy Research Institute, 2021)
This profile provides an assessment of a country’s potential to report on national-level coverage1 for a set of 16 nutrition interventions and recommends key actions to strengthen coverage measurement. Intervention coverage data is essential for tracking implementation and impact of strategies and investments to reduce malnutrition.